Overview of historical archeology in Mendoza - García, Alejandro (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2021)
The archeology of historical times has acquired a marked development in recent times, and the province of Mendoza has not been left out of this advance. These studies cover both indigenous and Spanish-Creole contexts and have been carried out by various researchers and from different theoretical perspectives. They also cover various geographical sectors of the province and are linked to the analysis of very different sites and activities. In order to reach a global understanding of this development, in this occasion this paper offers a brief overview of the study of sites or contexts of historical times from the analysis of some metadata, and evaluate the keys to the advancement of the historical archeology of Mendoza recorded fundamentally in the last 30 years. In addition, it explores some aspects related to the quantity and quality of bibliographic production in this field of study, as well as the role and implications of the theoretical position of the researchers involved. The result of the analysis constitutes a basic description of the state of progress of these studies and offers a diagnosis that allows the detection of some points that can be improved.